A proposed framework for FTMSK alumni / Fazleen Noorhuda Abdul Majid - Abdul Majid, Fazleen Noorhuda (2005)
Providing a good online service requires access to lots of data. At most organizations, this data is spread among different data store and in different data formats. To solve the problem, a repository can be used as a data layer in order to define a generic representation of a data store. Basically, the purpose of this research is to investigate the concept of repository and propose FTMSK Alumni information repository framework. The framework can be used as a guideline to develop FTMSK Alumni website, which share a common business model and required database, electronic document and workflow, and internet functionality. The framework is based on information repository which store accesses and manages information sources and/or information processes. Repository item are used to access data by identifying the detailed object of each items. Consequently, all the related information can be captured by the repository and most importantly, accessing data has to be easy